Does Muscular Force of the Upper Body Increase Following Acute, Direct Vibration? - Cochrane, D. J. (International Journal of Sports Medicine, 2016)
The aim of the current study was to examine the acute effect of direct vibration has on bicep curl force-generating capacity. 11 healthy team and individual sport-trained males performed right and left DB bicep curl at 50% of 1 RM where peak force (PF), mean force (MF), rate of force development (RFD) and electromyography (EMG) were assessed during the concentric phase before and immediately after direct vibration. Using new vibration technology utilizing a pulsing frequency (0–170 Hz) each arm was randomly assigned to receive either 10 min of direct vibration or control (no vibration). Following direct vibration PF increased 6.6±4.5 N (difference pre-post±90 CL; p>0.05) compared to control FP (−1.2±65 N; p>0.05) however, this was not significant. Furthermore, there were no other significant changes (p>0.05) in MP, RFD and EMG between vibration and control arms. This is in agreement with other research that has reported that acute strength changes from vibration elicits negligible changes, however it appears that there are no detrimental effects of using this new vibration device.
Keywords: strength; rate of force development; preacher curl; biceps brachii